2020
DOI: 10.1167/jov.20.12.2
|View full text |Cite
|
Sign up to set email alerts
|

A review of interactions between peripheral and foveal vision

Abstract: Visual processing varies dramatically across the visual field. These differences start in the retina and continue all the way to the visual cortex. Despite these differences in processing, the perceptual experience of humans is remarkably stable and continuous across the visual field. Research in the last decade has shown that processing in peripheral and foveal vision is not independent, but is more directly connected than previously thought. We address three core questions on how peripheral and foveal vision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 257 publications
(367 reference statements)
5
81
0
Order By: Relevance
“…In the case of distractor suppression, the short-term memory system would be responsible for the almost instantaneous buildup of local inhibition at likely distractor locations, whereas the long-term memory system would be responsible for its stability over longer time periods. Notice that the fact that humans can learn both quickly and stably is clearly established in the case of sensorimotor contingencies—for instance, in the case of saccade adaptation (e.g., McLaughlin, 1967 ) or transsaccadic perceptual recalibration (Valsecchi et al, 2020 ). Accordingly, it has been suggested that the capacity to learn at different time scales is a general property of the nervous system, from low-level sensorimotor learning, to higher-level cognitive learning (Kording et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of distractor suppression, the short-term memory system would be responsible for the almost instantaneous buildup of local inhibition at likely distractor locations, whereas the long-term memory system would be responsible for its stability over longer time periods. Notice that the fact that humans can learn both quickly and stably is clearly established in the case of sensorimotor contingencies—for instance, in the case of saccade adaptation (e.g., McLaughlin, 1967 ) or transsaccadic perceptual recalibration (Valsecchi et al, 2020 ). Accordingly, it has been suggested that the capacity to learn at different time scales is a general property of the nervous system, from low-level sensorimotor learning, to higher-level cognitive learning (Kording et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…How is it possible that humans can recognize objects and people in their peripheral view even though retinal resolution is relatively low there? Answers to this question focus on the special role of previous experience gathered while moving the eyes (e.g., Stewart, Valsecchi, & Schütz, 2020 ; von Helmholtz, 1925 ). It has been suggested that these experiences are used by a transsaccadic prediction mechanism to facilitate peripheral object recognition ( Herwig & Schneider, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…With every saccade, the presaccadic stimulus features and location must be reconciled with their postsaccadic counterpart in order to maintain a stable percept of the world. The visual system may achieve this transsaccadic perceptual stability by integrating pre- and postsaccadic feature information (Demeyer, Graef, Wagemans, & Verfaillie, 2010a; Ganmor, Landy, & Simoncelli, 2015 ; Wijdenes, Marshall, & Bays, 2015 ; Wolf & Schütz, 2015 ; Stewart, Valsecchi & Schütz, in press ) or location information ( Cicchini, Binda, Burr, & Morrone, 2013 ; Prime, Niemeier, & Crawford, 2005 ), or by suppressing small displacements that occur during the saccade ( Bridgeman, Hendry, & Stark, 1975 ). However, it is unknown when such mechanisms develop.…”
Section: Introductionmentioning
confidence: 99%
“…However, transsaccadic feature integration is not necessarily an automatic process and may not occur without specific task demands ( Stewart & Schütz, 2018b ; Stewart & Schütz, 2019b ; Stewart, Valsecchi & Schütz, in press ); similarly, it is not mandatory for pre- and postsaccadic location information to be fully integrated. This leads to the “under which conditions” part of the above question.…”
Section: Introductionmentioning
confidence: 99%